2018
DOI: 10.1093/jhps/hny013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a non-image-guided diagnostic hip injection in patients with clinical and radiographic evidence of intra-articular hip pathology

Abstract: The purpose of this study was to determine the likelihood of pain relief, as a measure of accurate diagnosis of intra-articular hip pathology and correct needle placement, with a non-image-guided intra-articular hip injection performed bedside in the clinic. A retrospective study of prospectively collected data was performed in a consecutive cohort of patients diagnosed with symptomatic intra-articular hip pathology who underwent a non-image-guided intra-articular injection in the clinic. All patients had clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Non–image guided intra-articular hip injections were given based on anatomic landmarks as previously described. 22 , 30 In a previous study using this same technique, we found that 96% of patients with intra-articular hip abnormalities experienced at least 70% improvement in pain after a corticosteroid injection, thereby proving the efficacy of the non–image guided technique. 22 Patients were advised to significantly reduce physical activity for 2 to 3 days after each injection and were instructed to avoid blood-thinning medications 2 days before and 5 days after the injections, including aspirin and NSAIDs.…”
Section: Methodsmentioning
confidence: 72%
“…Non–image guided intra-articular hip injections were given based on anatomic landmarks as previously described. 22 , 30 In a previous study using this same technique, we found that 96% of patients with intra-articular hip abnormalities experienced at least 70% improvement in pain after a corticosteroid injection, thereby proving the efficacy of the non–image guided technique. 22 Patients were advised to significantly reduce physical activity for 2 to 3 days after each injection and were instructed to avoid blood-thinning medications 2 days before and 5 days after the injections, including aspirin and NSAIDs.…”
Section: Methodsmentioning
confidence: 72%
“…One of the most common nonsurgical methods for the treatment of osteoarthritis includes pain‐related interventions such as intra‐articular injection of platelet‐rich plasma, hyaluronic acid, and analgesic agents often in combination with corticosteroids 15,16 . Intra‐articular injections may be image guided (usually ultrasound or fluoroscopic) or non‐image guided when performed in the office; however, most reports suggest that image‐guided intra‐articular injections are more accurate 17–22 …”
Section: Introductionmentioning
confidence: 99%
“…15,16 Intra-articular injections may be image guided (usually ultrasound or fluoroscopic) or non-image guided when performed in the office; however, most reports suggest that image-guided intraarticular injections are more accurate. [17][18][19][20][21][22] The hip, knee, and glenohumeral joints are large joints, and as a result, the distance from the skin to the joint may be affected by patient habitus and obesity. A patient may need to have a repeated needle stick with a needle of the appropriate length if the original needle used was too short to achieve an intra-articular injection even with compression of the soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 The potent anti-inflammatory properties of corticosteroids are effective in relieving pain secondary to intra-articular pathology, 26 reducing postoperative analgesic consumption and pain scores, 13,20 and elucidating the origin of knee pain for clinical decision-making purposes. 15 However, there is some concern that corticosteroids suppress the intra-articular immune response, making the joint vulnerable to postoperative infection. 29 , 30 The increased risk of infection after preoperative CSI has been validated in the arthroplasty literature.…”
mentioning
confidence: 99%